Characterizing the atmospheric conditions during the 2010 heatwave in Rio de Janeiro marked by excessive mortality rates - Geirinhas, João L.; Trigo, Ricardo M.; Libonati, Renata; Castro, Lucas C.O.; Sousa, Pedro M.; Coelho, Caio A.S.; Peres, Leonardo F.; Magalhães, Mônica de Avelar F.M. (The Science of the total environment, 2019)
Global temperatures have increased considerably over the last decades, directly impacting the number, intensity and duration of extreme events such as heat waves. Climate model projections accounting for anthropogenic factors indicate that deadly mega-heat waves are likely to become more frequent in the future. Although the atmospheric features and social-economic related impacts of heat waves have already been documented in various regions around the world, for other highly populated regions, such as the Metropolitan Region of Rio de Janeiro (MRRJ), a similar objective assessment is still needed. Heat waves directly impact the public health sector and particularly the less wealthy and elderly population groups. During February 2010, an elevated mortality peak occurred during a 8-day period (from 2 to 9 Feb 2010) characterized as a heat wave episode in MRRJ. A total excess of 737 deaths was recorded with the elderly group registering the highest mortality incidence. During this heat wave period, a quasi-stationary anticyclonic anomaly forced in altitude by a Rossby wave train was established over the south Brazilian coast. At the surface, the meteorological scenario from January 2010 to the heat wave period was marked by clear sky conditions, large precipitation deficits, and enhanced diabatic heating. During the heat wave period, warm and dry air masses were advected from interior regions towards the MRRJ, exacerbating temperature conditions by pronounced subsidence and adiabatic heating mechanisms. All these conditions contributed to pronounced positive temperature anomalies, reinforced by land-atmosphere feedbacks. [Display omitted] •A total of 3006 deaths was recorded representing an excess of 737 deaths.•Higher mortality risk for women compared to men and particularly for the elderly•Quasi-stationary mid-atmospheric anticyclonic anomaly over the South Atlantic•Relevant soil-atmosphere feedback mechanisms for the Heat Wave development•Regional katabatic winds were responsible for heating the already warm air mass.